2021
DOI: 10.1007/s10533-021-00867-8
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning benthic nitrogen cycle processes among three common macrofauna holobionts

Abstract: effect). Taken together, these functions promoted a reuse of nutrients at the benthic level, limiting net losses (e.g. denitrification) and effluxes to bottom water. Finally, the detection of multiple N transformations in macrofauna holobionts suggested a community-associated versatile microbiome, however, its role was of minor importance as compared to the activity of sediment-associated microbial communities. The present study highlights hidden and interactive effects among microbes and macrofauna, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 88 publications
(135 reference statements)
2
10
0
Order By: Relevance
“…Denitrification rates in coastal systems exhibit significant spatial and seasonal variability influenced by various factors. These include the fluctuating availability of NO 3 in the water column, which tends to be higher during colder periods, variations in macrofauna diversity, abundance, and biomass, diverse organic matter inputs from the water column, and varying water temperatures (Bonaglia et al, 2014b;Bartoli et al, 2021;Zilius et al, 2022). Results from this study suggest that the rise in water temperature played a significant role in the elevated denitrification rates observed during the summer in the Vistula plume area (Figure 4).…”
Section: Seasonality Of Nitrate Reduction Rates In Sediments Within T...mentioning
confidence: 66%
See 3 more Smart Citations
“…Denitrification rates in coastal systems exhibit significant spatial and seasonal variability influenced by various factors. These include the fluctuating availability of NO 3 in the water column, which tends to be higher during colder periods, variations in macrofauna diversity, abundance, and biomass, diverse organic matter inputs from the water column, and varying water temperatures (Bonaglia et al, 2014b;Bartoli et al, 2021;Zilius et al, 2022). Results from this study suggest that the rise in water temperature played a significant role in the elevated denitrification rates observed during the summer in the Vistula plume area (Figure 4).…”
Section: Seasonality Of Nitrate Reduction Rates In Sediments Within T...mentioning
confidence: 66%
“…In comparison, the contribution of D w to total denitrification was relatively minor at the study site due to relatively low NO 3 concentrations in bottom water, never exceeding 10 μM. In other coastal areas, the large dilution of riverine nitrate inputs results in limited rates of D w and the dominance of D n (Hietanen and Kuparinen, 2008;Zilius et al, 2022). D n has a complex regulation that depends on the availability of O 2 and NH 4 + in the pore water, which impacts nitrification rates and the proximity of the denitrification zone.…”
Section: Seasonality Of Nitrate Reduction Rates In Sediments Within T...mentioning
confidence: 82%
See 2 more Smart Citations
“…However, several studies report a positive relationship between macrofaunal biomass and sediment NH 4 + effluxes (e.g. Gibbs et al, 2005;Norkko et al, 2013), and benthic excretion and activity have been shown to stimulate macrobenthic (Norkko et al, 2001), meiobenthic, and microbial activity and enhance sediment biogeochemical cycling (Henriksen et al, 1983;Stief, 2013;Zilius et al, 2022). In our case, the high excretion rates of NH 4 -N in comparison to sediment efflux emphasize that the benthic fauna likely enhances nitrification, as indicated by the effluxes of nitrate and nitrite from the sediments (Figure S3).…”
Section: Both Speciesmentioning
confidence: 99%